2017
DOI: 10.1098/rspa.2016.0726
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired turbine blades offer new perspectives for wind energy

Abstract: Wind energy is becoming a significant alternative solution for future energy production. Modern turbines now benefit from engineering expertise, and a large variety of different models exists, depending on the context and needs. However, classical wind turbines are designed to operate within a narrow zone centred around their optimal working point. This limitation prevents the use of sites with variable wind to harvest energy, involving significant energetic and economic losses. Here, we present a new type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 30 publications
0
17
0
1
Order By: Relevance
“…In fact, small blade movements have been cancelled, so the energy losses are lower and an increased force is acting on the turbine. Conversely, this could be an argument proving that passive blade deformation or movement can increase the working range of the turbine as recently suggested by Cognet et al [37] in the wind energy framework. This suppression of small blade movements probably also explain the lower fluctuations of C P and C T experienced by the actual turbine for the higher T SR.…”
Section: Force and Torque Measurements Single Turbine Comparisons Wimentioning
confidence: 81%
“…In fact, small blade movements have been cancelled, so the energy losses are lower and an increased force is acting on the turbine. Conversely, this could be an argument proving that passive blade deformation or movement can increase the working range of the turbine as recently suggested by Cognet et al [37] in the wind energy framework. This suppression of small blade movements probably also explain the lower fluctuations of C P and C T experienced by the actual turbine for the higher T SR.…”
Section: Force and Torque Measurements Single Turbine Comparisons Wimentioning
confidence: 81%
“…This paper presents the computational numerical investigation of the bio-inspired vertical axis wind turbine in 2D in order to study the credibility of the proposed design relative to proposed morphology and outline design feature. Literature review indicated that bio inspired wind turbine design has improved the efficiency of the turbine as shown in research conducted by Fish, et al [20] and V. Cognet [21]. In this research the proposed design was modelled using Savonius wind turbine's configuration as reference and benchmark.…”
Section: Introductionmentioning
confidence: 94%
“…Wind turbines tend to be subject to deflections due to aerodynamic loading during operations, and the use of flexible blades as a form of passive pitch control has been previously explored. Wind tunnel studies have shown that an elasto-flexible lifting surface increases the chamber thus increases lifting capabilities and postpones stall onset [7], preventing the sudden drop in lift, and has been shown to increase the energy production of the wind turbine by up to 35% [8].…”
Section: Flexible Bladesmentioning
confidence: 99%